Eksplorasi Etnomatematika Tarian Nganjan dalam Upacara Adat Dall’o Pada Masyarakat Suku Dayak Uud Danum di Kecematan Serawai Kabupaten Sintang - Tira, Anastasia; Liliana, Sepriani (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to describe the mathematical elements contained in the Nganjan Dance performed during the Dall’o Dayak Uud Danum traditional ceremony in Serawai District, Sintang Regency. The method used is qualitative research with an ethnographic approach, involving observation, semi-structured interviews, and documentation to collect data from three informants. The results of the study indicate that the Nganjan Dance encompasses various fundamental mathematical activities such as calculating, measuring, designing, determining location, playing, and explaining. The identified mathematical elements in this dance include angles, geometric transformations, plane figures, and three-dimensional shapes. Each dance movement carries mathematical meaning that can be analyzed, such as the angular patterns formed in the movements and the use of geometric formations that demonstrate the relationship between dance and mathematics. The conclusion of this study is that the Nganjan Dance is not only a form of cultural expression but also contains mathematical elements that can enhance the public’s, especially students’, understanding of mathematical concepts within the context of local culture.